2023
DOI: 10.7759/cureus.35490
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Wave Elastography for the Diagnosis of Pediatric Hashimoto’s Thyroiditis: A Systematic Review and Meta-Analysis

Abstract: Shear-wave elastography (SWE) has emerged as a novel ultrasonographic technique for the diagnosis of pediatric Hashimoto's Thyroiditis (HT). This systematic review and meta-analysis aim to summarize current evidence to determine the diagnostic value of SWE for HT. MEDLINE, a comprehensive search yielded five studies inclusive of 392 subjects. A meta-analysis comparing SWE values (kPa) between children with HT and healthy controls yielded a Cohen's d-value of 1.34 (CI 1.02-1.65), suggesting statistically signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Compared with conventional ultrasound examination, high-frequency ultrasonic elastography exhibited a significantly higher diagnostic accuracy of HT (sensitivity, 92.16%; specificity, 92.86%; NPV, 86.67%; PPV, 95.92%)[ 94 ]. A recent meta-analysis indicated that ultrasound-based shear wave elastography plays an important role and should be encouraged for use in diagnosing pediatric HT[ 95 ].…”
Section: Ultrasonography Application In Aitdmentioning
confidence: 99%
“…Compared with conventional ultrasound examination, high-frequency ultrasonic elastography exhibited a significantly higher diagnostic accuracy of HT (sensitivity, 92.16%; specificity, 92.86%; NPV, 86.67%; PPV, 95.92%)[ 94 ]. A recent meta-analysis indicated that ultrasound-based shear wave elastography plays an important role and should be encouraged for use in diagnosing pediatric HT[ 95 ].…”
Section: Ultrasonography Application In Aitdmentioning
confidence: 99%